THE USE OF TRANEXAMIC ACID IN RADICAL PROSTATECTOMY - Yancheuski P.; Byk V. S.; Polyuhovich D. A.; Khilmanovich S. (Žurnal Grodnenskogo Gosudarstvennogo Medicinskogo Universiteta, 2019)
The aim of the study was to evaluate the effectiveness of reducing blood loss when using tranexamic acid when performing radical prostatectomy. Material and methods. We examined 37 patients after surgery - radical prostatectomy in the pre and postoperative period. The control group (15 people) included patients with standard prophylaxis of thromboembolic complications and standard perioperative therapy. The study group included 22 patients, to whom standard therapy was supplemented with intravenous administration of Tranexam® dispenser 1000 in 20 minutes. Results. The indicators of the general analysis of the blood and coagulation system of patients with prostate tumors were considered. Intravenous infusion of tranexamic acid enables to reduce operative blood loss in patients when performing radical prosatectomy. Conclusions. The obtained data enable to consider the use of tranexamic acid to be justified in order to reduce operating blood loss.